Linear-elastic stress field of notched concrete beam : An application of finite element in theory of critical distances - Mohamad Shazwan, Ahmad Shah; Norhazilan, Md. Noor; Mohd. Nasir, Tamin; Ahmad Kueh, Beng Hong; Libriati, Zardasti; Nordin, Yahaya (IOP Publishing, 2021)
Fatigue failures occur in all structures including brittle and ductile structures. However, the study on fatigue in ductile material like metal and steel has tremendously developed compared to brittle material such as concrete. Fortunately, the Theory of Critical Distance (TCD) is witnessed successfully assess fatigue fracture in concrete. In obtaining one of the outputs using TCD which is critical distance, fatigue limit of concrete that is obtained through laboratory testing and stress field generated using computational analysis engineering software (CAE) are required. In this article, the concern will be on producing the valid and reliable stress field data since inaccurate input into the CAE will result unreliable output that is exposed to errors. In order to guarantee the result is accurate, validation works were conducted in preprocess and post-process phase while analysing finite model using ABAQUS. As the outputs comply accordingly based on the validation works, the critical distance is confidence to be consumed for the subsequent research related to TCD.